Meaningful learning theory as a proposal for innovation in nursing education: student experience - Diana Paula de Souza Rego Pinto Carvalho; Anna Larissa de Castro Rego; Kalyane da Silva Ferreira; Sérgio Balbino da Silva; Allyne Fortes Vitor; Marcos Antonio Ferreira Júnior (Universidade Federal de Santa Maria, 2015)
Aim: to report the experience of scholarship students participating in the project "Building concepts in undergraduate nursing education in the light of the theory of meaningful learning: construction of concept maps using the Cmap Tools® software". Method: report of experience of scholarship students about a project included in the Integrated Action Notice published by an institution of higher education and developed between the months of January to September 2013. Results: these are presented in three axes proposed by the project: teaching, research and extension. Thus, there was a minicourse on conceptual maps and instruction on the software, the production of scientific papers on the topic addressed and the contribution of scholarship students in scientific studies. Final considerations: the scholarship students reflected on the teaching-learning process, with bases directed to the learner, since it constitutes the subject in training to actively participate in building their cognitive structure